The Meaning Of Indonesia’s-Foreign-Policy-Themed Political Cartoon Artwork During Demokrasi Terpimpin Era - Taufan Hidayatullah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Mass media uses political cartoon as a strategy to convey opinion regarding an issue with humour or satirical approach. This research aims to understand the meaning of caricature artwork published in newspapers during Demokrasi Terpimpin (Orde Lama) that criticize Indonesia’s foreign policy. During the era, President Soekarno implemented a confrontative Indonesian foreign policy. To understand the meaning of those foreign-policy-themed political cartoon, an Iconographic theory by Erwin Panofsky using descriptive analysis method is used. The research conducted through several steps which include pre-iconographic description, iconographic analysis, and iconological interpretation. The discussion begins by describing the visual aspects of political cartoons. The next stage explains the visual analysis and ends by interpreting the visual metaphors of political cartoons.From the research, Indonesia’s foreign policy during Demokrasi Terpimpin era showed assertive and critical attitude towards (neo) imperialism and colonialism. The benefits of this research is to give a deeper understanding about Indonesia’s foreign policy especially during Demokrasi Terpimpin era through political cartoons artwork.